Global Burden of Atherosclerotic Cardiovascular Disease in People Living With HIV: Systematic Review and Meta-Analysis. Issue 11 (11th September 2018) - Shah, Anoop S.V.; Stelzle, Dominik; Lee, Kuan Ken; Beck, Eduard J.; Alam, Shirjel; Clifford, Sarah; Longenecker, Chris T.; Strachan, Fiona; Bagchi, Shashwatee; Whiteley, William; Rajagopalan, Sanjay; Kottilil, Shyamasundaran; et al.
Abstract : Background: With advances in antiretroviral therapy, most deaths in people with HIV are now attributable to noncommunicable illnesses, especially cardiovascular disease. We determine the association between HIV and cardiovascular disease, and estimate the national, regional, and global burden of cardiovascular disease attributable to HIV. Methods: We conducted a systematic review across 5 databases from inception to August 2016 for longitudinal studies of cardiovascular disease in HIV infection. A random-effects meta-analysis across 80 studies was used to derive the pooled rate and risk of cardiovascular disease in people living with HIV. We then estimated the temporal changes in the population-attributable fraction and disability-adjusted life-years (DALYs) from HIV-associated cardiovascular disease from 1990 to 2015 at a regional and global level. National cardiovascular DALYs associated with HIV for 2015 were derived for 154 of the 193 United Nations member states. The main outcome measure was the pooled estimate of the rate and risk of cardiovascular disease in people living with HIV and the national, regional, and global estimates of DALYs from cardiovascular disease associated with HIV. Results: In 793 635 people living with HIV and a total follow-up of 3.5 million person-years, the crude rate of cardiovascular disease was 61.8 (95% CI, 45.8–83.4) per 10 000 person-years. In comparison with individuals without HIV, the risk ratio for cardiovascular disease was 2.16 (95% CI, 1.68–2.77). Over the past 26 years, the global population–attributable fraction from cardiovascular disease attributable to HIV increased from 0.36% (95% CI, 0.21%–0.56%) to 0.92% (95% CI, 0.55%–1.41%), and DALYs increased from 0.74 (95% CI, 0.44–1.16) to 2.57 (95% CI, 1.53–3.92) million. There was marked regional variation with most DALYs lost in sub-Saharan Africa (0.87 million, 95% CI, 0.43–1.70) and the Asia Pacific (0.39 million, 95% CI, 0.23–0.62) regions. The highest population-attributable fraction and burden were observed in Swaziland, Botswana, and Lesotho. Conclusions: People living with HIV are twice as likely to develop cardiovascular disease. The global burden of HIV-associated cardiovascular disease has tripled over the past 2 decades and is now responsible for 2.6 million DALYs per annum with the greatest impact in sub-Saharan Africa and the Asia Pacific regions. Clinical Trial Registration: URL:https://www.crd.york.ac.uk/prospero . Unique identifier: CRD42016048257. Abstract : Supplemental Digital Content is available in the text.